PERAN STAKEHOLDER DALAM MENDUKUNG KETAHANAN MANGROVE BERKELANJUTAN DI BANYUURIP MANGROVE CENTER, JAWA TIMUR - Hendrik Suhendri; Dito Aditia; Cakti Indra Gunawan (KRISNA: Kumpulan Riset Akuntansi, 2025)
The area of mangrove forests in Indonesia continues to shrink, so it is necessary to strengthen the capacity of human resources to support sustainable mangrove resilience. The purpose of the research is to identify multi-stakeholder roles, strengths, weaknesses, opportunities and threats, as well as formulate the best strategies in supporting sustainable mangrove resilience. This study uses a descriptive qualitative method, with SWOT analysis. The results of the study showed that there were multi-staleholders who played a role, namely the community, the Banyuurip Village Government, the Banyuurip Mangrove Center Admin Team, the Non-Governmental Organization Volunteer Alliance for Nature Rescue (Arupa), PGN Saka, Academicians of Brawijaya University, Academicians of Raden Rahmat University, Mass Media, namely Mongabay, and the Forestry Service of East Java Province. Banyuurip Mangrove Center has 11 strengths, 8 weaknesses, 12 opportunities and 4 threats. The best strategy formulation is to strengthen synergy between stakeholders through communication forums